2013
DOI: 10.5812/hepatmon.7612
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Hepatocellular Carcinoma in a Middle Eastern Population

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the leading causes of death in Saudi male patients. Local clinical and demographic data of this disease are scarce.ObjectivesWe sought to describe the clinical characteristics and outcomes of patients from two tertiary care centers in Saudi Arabia.Patients and MethodsData were collected for all patients diagnosed to have hepatocellular carcinoma between June 2003 and July 2008 who had been registered in a special research database (the Saudi Observatory Liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
24
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 44 publications
14
24
2
2
Order By: Relevance
“…In this study, in HCC patients aged 41‐60 years old, there were 480 (83.92%) males and 92 (16.08%) females, and in HCC patients ≥61 years old, there were 435 (72.62%) males and 164 (27.38%) females. This study revealed that HCC was more prevalent in males, which is in agreement with previous studies, as well as other local and regional studies …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, in HCC patients aged 41‐60 years old, there were 480 (83.92%) males and 92 (16.08%) females, and in HCC patients ≥61 years old, there were 435 (72.62%) males and 164 (27.38%) females. This study revealed that HCC was more prevalent in males, which is in agreement with previous studies, as well as other local and regional studies …”
Section: Discussionsupporting
confidence: 94%
“…This study revealed that HCC was more prevalent in males, which is in agreement with previous studies, 16,17 as well as other local and regional studies. 18,19 In addition, the finding that females were significantly older than males might also refect a course in disease progression. Previous studies have shown that the liver fibrosis status of women changes with age, which may be due to changes in the reproductive status, 20 Therefore, less treatment measures will affect the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…China has the highest incidence of HCC in the world, accounting for more than 40% of all HCC cases and 55% of liver cancer deaths [3,4] . Southern European countries have an intermediateincidence (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) cases per 100,000 population/year); while North America, South America, Northern Europe, and parts of Middle East have low-incidence rates (< 5 cases per 100,000 population/year) [3][4][5] . The incidence in Asian countries tends to decline in the past 2 decades whilst it increased in United States and Canada because of high rate of chronic hepatitis C virus (HCV)-related cirrhosis, nonalcoholic fatty liver disease and immigrants from HBV endemic regions [4] .…”
Section: Global Epidemiology and Burden Of Hccmentioning
confidence: 99%
“…The median age of diagnosis is 66 years [12] . The results of a tertiary center in Saudi Arabia showed that most of the patients diagnosed with HCC presented at late tumor stages with advanced liver disease and had poor prognosis with an average of 33-month survival [12] . This prompts the implementation of HCC surveillance strategies in this geographic region.…”
Section: Epidemiology and Burden Of Disease In The Eastern Mediterranmentioning
confidence: 99%
“…This implementation is expected to result in a significant drop in HBV-related HCC cases in Saud Arabia. Similarly, chronic hepatitis C (CHC)-related liver cirrhosis and HCC are also frequently reported in Saudi Arabia [9]- [11]. The presentation of HCC can be variable, ranging from small focal liver lesions that could be detected during routine radiological screenings of cirrhotic patients to advanced disease with severe local invasion or even distant metastasis [3] [12] [13].…”
Section: Introductionmentioning
confidence: 99%